Secondary School Violence Among Adolescents: The Contributing Factors and Way Forward - Ajani, Babatunde Adewole; Umanhonlen, Sylvester E.; Raji, Naseem Akorede; Adegoke, Solomon Ayodeji; Adewuyi, Habeeb Omoponle (Universitas Pendidikan Indonesia (UPI), 2024)
The school, which should be a relatively safe place where students can learn and grow, is gradually becoming a place of violence and fear. This study examined the pattern of relationship between school climate, peer influence, parental socio-economic status, and school violence. This study employed a descriptive survey of correlational design, and a multistage sampling procedure was utilized. Adolescents (N = 286; 40.9% female, 59.1% male) aged 11 to 17 took part. Participants completed standardized instruments: (School Climate Scale α = 0.84; Peer Influence Scale α = 0.80; Parental Socio-economic Status Scale α = 0.88; and Violent Behavior rating Scale α = 0.91). The results showed that school climate (r =0.246, p0.05); socio-economic status (r =0.459, p 0.05), and peer influence (r =0.575, p0.05) all had a significant relationship with school violence. Also, peer influence recorded the most significant relative contribution to school violence, followed by school climate and parental socio-economic status, respectively. The study concluded that preventing school violence requires comprehensive and all-encompassing approaches, as addressing the problem with a single factor is unlikely to be sufficient.